Changes in Family Relationships among Substance Abusing Runaway Adolescents: A Comparison between Family and Individual Therapies. (16th May 2015) - Guo, Xiamei; Slesnick, Natasha; Feng, Xin
Abstract : Eligible adolescents (12–17 years old) were recruited from a short‐term crisis shelter for runaway adolescents in a large Midwestern city. Adolescents ( N = 179) were randomly assigned to Ecologically‐Based Family Therapy (EBFT, n = 61), the Community Reinforcement Approach (CRA, n = 57), or brief Motivational Enhancement Therapy (MET, n = 61) with the primary focus on substance abuse. A significant increase in perceived family cohesion and a significant reduction in perceived family conflict were found among all treatment conditions from baseline to the 24‐month follow‐up. Adolescents who received EBFT demonstrated more improvement in family cohesion after treatment than those who received CRA or MET, and more reduction in family conflict during treatment than those who received MET.